Development of an Emergency Department Trigger Tool Using a Systematic Search and Modified Delphi Process. Issue 1 (March 2020) - Griffey, Richard Thomas; Schneider, Ryan M.; Adler, Lee M.; Capp, Roberta; Carpenter, Christopher R.; Farmer, Brenna M.; Groner, Kathyrn Y.; Hodkins, Sheridan; McCammon, Craig A.; Powell, Jonathan T.; Sather, Jonathan E.; Schuur, Jeremiah D.; et al.
Abstract : Objective: This study aimed to develop an emergency department (ED) trigger tool to improve the identification of adverse events in the ED and that can be used to direct patient safety and quality improvement. This work describes the first step toward the development of an ED all-cause harm measurement tool by experts in the field. Methods: We identified a multidisciplinary group of emergency medicine safety experts from whom we solicited candidate triggers. We then conducted a modified Delphi process consisting of 4 stages as follows: (1) a systematic literature search and review, including an independent oversampling of review for inclusion, (2) solicitation of empiric triggers from participants, (3) a Web-based survey ranking triggers on specific performance constructs, and (4) a final in-person meeting to arrive at consensus triggers for testing. Results of each step were shared with participants between each stage. Results: Among an initial 804 unique articles found using our search criteria, we identified 94 that were suitable for further review. Interrater reliability was high (κ = 0.80). Review of these articles yielded 56 candidate triggers. These were supplemented by 58 participant-submitted triggers yielding a total of 114 candidate triggers that were shared with team members electronically along with their definitions. Team members then voted on each measure via a Web-based survey, ranking triggers on their face validity, utility for quality improvement, and fidelity (sensitivity/specificity). Participants were also provided the ability to flag any trigger about which they had questions or they felt merited further discussion at the in-person meeting. Triggers were ranked by combining the first 2 categories (face validity and utility), and information on fidelity was reviewed for decision making at the in-person meeting. Seven redundant triggers were eliminated. At an in-person meeting including representatives from all facilities, we presented the 50 top-ranked triggers as well as those that were flagged on the survey by 2 or more participants. We reviewed each trigger individually, identifying 41 triggers about which there was a clear agreement for inclusion. Of the seven additional triggers that required subsequent voting via e-mail, 5 were adopted, arriving at a total of 46 consensus-derived triggers. Conclusions: Our modified Delphi process resulted in the identification of 46 final triggers for the detection of adverse events among ED patients. These triggers should be pilot field tested to quantify their individual and collective performance in detecting all-cause harm to ED patients.